Five-year outcomes of double kissing mini-culotte stenting vs. mini-culotte stenting using drug-eluting stents for the treatment of true coronary bifurcation lesions - Tu, Sheng; Zhang, Linlin; Tian, Qingqing; Hu, Fudong; Wang, Ying; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2024)
Objective: To compare the clinical outcomes between Double Kissing Mini-culotte (DKMC) stenting and Mini-culotte (MC) stenting in treating patients with true coronary bifurcation lesions (CBLs) in the clinical real world.This retrospective observational cohort study included 180 consecutive patients with true CBLs (Medina type 1,1,1; 1,0,1; 0,1,1). All the eligible patients underwent coronary angiography and percutaneous coronary intervention with twostent techniques in our hospital, among whom 97 received DKMC treatment and 83 MC treatment. The primary clinical endpoints were the major adverse cardiovascular events (MACE), which included cardiac death, myocardial infarction, and target vessel/ lesion revascularization (TVR/TLR). The secondary endpoints were stent thrombosis, in-stent restenosis, and individual components of MACE.Results: Quantitative coronary angiography analysis (at 5 years) showed that late lumen loss (0.25±0.41mm vs.0.14±0.32mm, P=0.032), segmental diameter restenosis of side branch (27.84±12.34% vs.19.23±9.76%, P=0.016) in DKMC treatment were lower as compared with MC treatment. Notably, compared to MC treatment, the cumulative event rate of MACE at 5 years(22.8% vs.8.3%，P=0.007) and TVR/TLR (17.7% vs.6.3%, P=0.018) in DKMC treatment driven mainly by TVR/TLR. Especially, DKMC group was related to a significant reduction in the primary and secondary endpoints in patients with high-risk.DKMC treatment was associated with less late lumen loss and restenosis in the side branch, lower rate of cumulative MACE and TVR/TLR. DKMC treatment is more effective to treat true CBLs as compared to MC treatment but warranted to be further confiemed by a ramdamized clinical trial.